Prevalence of depressive symptoms and their associated factors among older adults in Yirgalem town, Southern Ethiopia: A community-based cross-sectional study - Mulugeta, Abiy; Azale, Telake; Mirkena, Yohannes; Koye, Selam; Nakie, Girum; Kassaye, Abenet; Dereje, Jerman; Bedewi, Neim; Dechasa, Deribe Bekele; Asfaw, Henock (Frontiers in Psychiatry, 2023)
Background Depression is a serious mental health issue and the largest contributor to disability worldwide. Elderly people with depression are significantly more likely to experience negative outcomes such as poor physical health, strained social relationships, and decreased quality of life. Studies on geriatric depression are limited in developing nations like Ethiopia. Objectives The purpose of this study was to determine the prevalence of depressive symptoms and associated factors among older adults in Yirgalem, Southern Ethiopia, in 2022. Methods A community-based cross-sectional study was conducted on a sample of 628 older adults in Yirgalem town from May 15 to June 15, 2022. The study subjects were selected using a multi-stage systematic sampling technique. Data were collected using the 15-item Geriatric depression scale through face-to-face interviews. The collected data were edited, cleaned, coded, and entered into Epi data version 4.6 software and analyzed using STATA version 14. Bivariable and multivariate logistic regression analysis was computed to identify factors associated with depression, and statistical significance was declared at a 95% confidence interval with a P-value less than 0.05. Results A total of 620 older adults were included in the study, with a response rate of 97.8%. The prevalence of depressive symptoms among older adults was 51.77% (95% CI: 47.83–55.69). Being a woman (AOR = 2.3, 95% CI: 1.56–3141); being of more advanced age: 70–79 years old (AOR = 1.92, 95% CI: 1.20–3.07), 80–89 years old (AOR = 2.15, 95% CI: 1.27–3.65), 90 and older (AOR = 3.77, 95% CI: 1.95–7.79); living alone (AOR = 1.99, 95% CI = 1.17–3.41); having a chronic illness (AOR = 3.24, 95% CI: 1.06–4.46); having anxiety (AOR = 3.40; 95% CI: 2.25–5.14); and having poor social support (AOR = 3.56, 95% CI: 2.09–6.04) were statistically associated with depressive symptoms at a P-value of less than 0.05. Conclusion This study found that depression affects more than half of the elderly residents in the study area. More advanced age, being a woman, living alone, having a chronic illness, having anxiety, and having poor social support were all strongly linked to depression. There is a need to integrate counseling and psychiatric services into the community healthcare system.